Analyzing complications and implementing solutions in a pediatric inguinal hernia cooperation program in Equatorial Guinea: a prospective cohort study - Jaime Rodríguez de Alarcón García; Amalia Úbeda Pascual; María Fanjul Gómez; Pablo Morató Robert; Rocío Espinosa Góngora; Ernesto Martínez García; Carlos Román Guerrero; Santiago Jaime Abaga Abaga; Carmen Soto Beauregard (SpringerOpen, 2023)
Abstract Background Few studies have evaluated the efficacy of short-term medical missions. This study was aimed to evaluate complication rates and determine the effects of protocol changes in a pediatric inguinal hernia campaign in Equatorial Guinea and analyze post-operative follow-up capacity. Methods In this prospective observational cohort study, we evaluated two patient cohorts (group A, 2017-2018; group B, 2019) treated during campaigns in Equatorial Guinea for congenital inguinal pathology (hernia, hydrocele, and cryptorchidism). Patients aged < 18 years treated in referral campaigns were included. Complications occurring up to 6 months post-operatively were evaluated. Two stages were defined: Stage 1, wherein, complication rate in group A was compared to that in a control group from a tertiary hospital in Spain (with a case-control ratio of 1:2, paired according to age, sex and diagnosis); stage 2, wherein, complication rates between groups A and B were compared. Group B received a single dose of prophylactic amoxicillin-clavulanic acid. Follow-up capacity was assessed through follow-up appointments. Results In stage 1, complication and surgical site infection (SSI) rates were 21.3% and 7.4% in group A (n = 94), and 5.8% (p < 0.001) and 0.5% (p = 0.012) in the control group, respectively. Group A had 20.2% loss-to-follow-up. In group B (n = 62), 6-month postoperative follow-up could not be assessed owing to restrictions due to the COVID-19 pandemic, so only early complications were considered in stage 2, were complication and surgical site infection rates were 18.1% and 7.4% in group A and 11.3% (p = 0.350) and 1.6% (p = 0.150) in group B. Conclusion Our results showed higher than expected complication rates. Pre-operative prophylactic antibiotic could not show to reduce SSI. Further studies are needed to reduce complication rates in these campaigns. Patient loss-to-follow-up ratio warrants considering new strategies.